Improving performance on core processes of care. Issue 3 (June 2016) - Austin, John Matthew; Pronovost, Peter J.
Abstract : Purpose of review: This article describes the recent literature on using extrinsic and intrinsic motivators to improve performance on core processes of care, highlighting literature that describes general frameworks for quality improvement work. Recent findings: The literature supporting the effectiveness of extrinsic motivators to improve quality is generally positive for public reporting of performance, with mixed results for pay-for-performance. A four-element quality improvement framework developed by The Armstrong Institute at Johns Hopkins Medicine was developed with intrinsic motivation in mind. The clear definition and communication of goals are important for quality improvement work. Training clinicians in improvement science, such as lean sigma, teamwork, or culture change provides clinicians with the skills they need to drive the improvement work. Peer learning communities offer the opportunity for clinicians to engage with each other and offer support in their work. The transparent reporting of performance helps ensure accountability of performance ranging from individual clinicians to governance. Summary: Quality improvement work that is led by and engages clinicians offers the opportunity for the work to be both meaningful and sustainable. The literature supports approaching quality improvement work in a systematic way, including the key elements of communication, infrastructure building, training, transparency, and accountability.